(3aJM GdCZdGb aj GdMK Ydi ecGQe GdCNdGbs - (3YHO GdQMef Hf CHj HcQ GdMfHdj GdOeTbj,J (B856 (3g` s ((3OQhjT Hf eMeO GdTGei s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdPi LGO hCfYe hHYO agPg CQHYhf MOjKkG EfJbjJgG ef cdGe SjO GdCfGe JJVef GdJQZjH ai GdNjQGJ GdJi jYXe KhGHgG hGdMSfGJ GdJi JaJM HgG ef GdSYGOI CHhGHgG s
(3BNQgG (B:s
(3GdMOjK GdCQHYhf Yf YHO Gddg Hf YeQh Hf GdYGU QVi Gddg YfgeG Cf QLdkG LGA Edi QShd Gddg Udi Gddg Ydjg hSde abGd Efi hbO HjfG Pdc ai QSGdJfG GdSja GdUGQe hGdMeO ddg QH GdYGdejf s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B123 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B252s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1111s
Keywords: (3GdMOjK h GdeUWdMs